Perbandingan Pemahaman Konsep Matematis Siswa pada Pembelajaran Kooperatif Tipe TPS dengan TSTS - Septiadi, Dimas Danar; Wahidah, Anisatil (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to determine the differences in students' mathematical concept understanding abilities between those using the TPS type cooperative learning model and the quadrilateral TSTS type material in class VII students of SMP Negeri 7 Jember. This research is a quantitative research, while the type of research used is a quasi-experimental design with the non-equivalent posttest-only control group design. The population of this study was all seventh grade students of SMP Negeri 7 Jember for the 2018/2019 academic year, which was divided into 9 classes with a total of 317 students. Sampling was carried out using purposive sampling technique by taking 2 classes from 9 classes with certain considerations. The experimental class I (VII-E) of 36 students was given the TPS type of cooperative learning model and the experimental class II (VII-C) of 36 students was given the TSTS type of cooperative learning model. The data collection technique used documentation and test instruments (posttest) in the form of a description test of 6 questions. The data analysis technique used descriptive statistical analysis and inferential statistical analysis, namely the Z test. The results of the research through descriptive statistical analysis showed the average posttest result in the class using the TPS type cooperative learning model was 58,456 while the average posttest result in the class using the learning model cooperative type TSTS is 58,331. The results of inferential data analysis showed that the statistical test value Z=0.046 was less than the critical value Z_((0.05))=1.960 or 0.046<1.960. So H_0 is accepted and H_a is rejected. This means that it can be concluded that the average ability to understand mathematical concepts of students is the same between classes that use the TPS type cooperative learning model and those using the TSTS type cooperative learning model in the quadrilateral material for class VII SMP Negeri 7 Jember.Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan pemahaman konsep matematis siswa antara yang menggunakan model pembelajaran kooperatif tipe TPS dan tipe TSTS materi segiempat pada siswa kelas VII SMP Negeri 7 Jember. Penelitian ini merupakan penelitian kuantitatif sedangkan jenis penelitian yang digunakan adalah quasi eksperimental design dengan desain penelitian the non-equivalent posttest-only control group design. Populasi penelitian ini seluruh siswa kelas VII SMP Negeri 7 Jember tahun pelajaran 2018/2019, yang terbagi atas 9 kelas dengan jumlah 317 siswa. Pengambilan sampel dilakukan dengan menggunakan teknik purposive sampling dengan mengambil 2 kelas dari 9 kelas dengan pertimbangan tertentu. Kelas eksperimen I (VII-E) sebanyak 36 siswa diberi model pembelajaran kooperatif tipe TPS dan kelas eksperimen II (VII-C) sebanyak 36 siswa diberi model pembelajaran kooperatif tipe TSTS. Teknik pengumpulan data menggunakan dokumentasi dan instrumen tes (posttest) berbentuk tes uraian sebanyak 6 butir soal. Teknik analisis data menggunakan analisis statistik deskriptif dan analisis statistik inferensial yaitu uji Z. Hasil penelitian melalui analisis statistik deskriptif menunjukkan rata-rata hasil posttest pada kelas yang menggunakan model pembelajaran kooperatif tipe TPS sebesar 6 sedangkan rata-rata hasil posttest pada kelas yang menggunakan model pembelajaran kooperatif tipe TSTS sebesar . Hasil analisis inferensial data menunjukkan bahwa nilai uji statistik kurang dari nilai kritis atau . Sehingga diterima dan ditolak. Artinya dapat disimpulkan bahwa rata-rata kemampuan pemahaman konsep matematis siswa sama antara kelas yang menggunakan model pembelajaran kooperatif tipe TPS dengan yang menggunakan model pembelajaran kooperatif tipe TSTS pada materi segiempat kelas VII SMP Negeri 7 Jember.